2021
DOI: 10.52586/5027
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in musculoskeletal conditions

Abstract: Artificial intelligence (AI) is an iterative process by which information is captured, transformed into knowledge and processed to produce adaptive changes in the environment. AI is a broad concept, involving virtual (computing) and physical (robotics) elements. In this narrative literature review, we focus on the aspects of AI that present major opportunities for developing health care. Within a few years, AI will be part of our daily clinical practice. Although significant advances are being made, the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…For instance, AI algorithms have been used to decode neural signals from residual limb muscles in amputees, enabling intuitive and natural control of prosthetic limbs ( 75 ). By analyzing muscle activation patterns, AI can predict the intended movement and execute the corresponding action in the prosthetic limb.…”
Section: Neuro-prostheticsmentioning
confidence: 99%
“…For instance, AI algorithms have been used to decode neural signals from residual limb muscles in amputees, enabling intuitive and natural control of prosthetic limbs ( 75 ). By analyzing muscle activation patterns, AI can predict the intended movement and execute the corresponding action in the prosthetic limb.…”
Section: Neuro-prostheticsmentioning
confidence: 99%
“…The introduction of artificial intelligence (AI) models for diagnosing medical conditions could reduce the burden on healthcare professionals and prevent oversights by alleviating the problem that traditional diagnoses are examiner-dependent [ 17 ]. There has already been success in utilizing AI for endoscopy, chest X-rays, and pathological examinations [ [18] , [19] , [20] , [21] ]. It has been reported that various AI models can facilitate clinical care for professionals, improving diagnosis and treatment for people with hemophilia [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various artificial intelligence (AI) algorithms have been employed to evaluate medical images. Machine learning is a subfield of AI that includes models that can learn patterns and improve themselves by making comparisons within the database provided ( 10 , 12 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In musculoskeletal radiology, a number of studies have investigated the use of AI in tasks such as the diagnosis/classification of fractures, the identification of ligament/meniscal injuries, and the improvement of radiologist workflows ( 12 ) .…”
Section: Introductionmentioning
confidence: 99%